THE FUTURE OF AFRICAN THEOLOGY: A TRIBUTE TO THE LEGACY OF MAGESA (Hekima Review, 2024)
In the past five years, we have witnessed the passing on of pioneering African theologians of the 20th century, John Mbiti +2019, Charles Nyamiti +2020, Laurenti Magesa +2022, Benezet Bujo +2024. This paper reflects on the future of African theology througha tribute to the legacy of one of them, namely Laurenti Magesa. It argues that if African theology is to have a compelling future, it should focus on “formation” through which these great African theologians received their theological training rather than education. The paper is part of Hekima’s commemoration of its 40th anniversary, so it also attempts to rethink the future of Hekima University College.